Some Mineralogical Characteristics of the Egyptian Black Sand Beach Ilmenite Part IΙ: Rutile-Ilmenite and the Various Titanhematite Grains - Moustafa, M. I. (Engineering, Technology & Applied Science Research, 2022)
In addition to the grains of homogeneous ilmenite, ferriilmenite, hematite-ilmenite exsolved intergrowths, and the partially altered ilmenite grains, other textures are detected in the separated ilmenite concentrate. The grains of rutile-ilmenite exsolved intergrowth represent 0.8% of the detected ilmenite grains. The ilmenite component of this intergrowth is detected to be ferriilmenite associated with geikielite, pyrophanite, and rutile, with Cr2O3 content ranging between 0 and 0.5%. The exsolved rutile is ferriforrous rutile composed of rutile, hematite, geikielite, and pyrophanite, its Cr2O3 content ranging between 0 and 0.4%. The detected individual titanhematite grains represent 4.4% and include 3 textures arranged, in a decreasing order of abundance, as: ilmenite-hematite, rutile-hematite, and rutile-ilmenite-hematite exsolution intergrowths. MgO and MnO have minimum values and they do not follow Fe2O3. In some homogeneous titanhematite or exsolved rutile-hematite, Fe2O3 content may be replaced with SiO2. In all titanhematite intergrown textures, the Cr2O3 content ranges between 0 and 0.1%. Only in the case of the titanhematite host with exsolved rutile, the contained MgO ranges between 1.2 and 5.3%. Some ferromagnetic titanhematite grains separated with the fraction of magnetite are detected. In these grains, the Cr2O3, MgO, and MnO contents range between 0-0.2, 0-3, and 0-1.4% respectively. Several varieties of chromite and chromspinel mineral grains are found and represent 1.1% of the detected bulk ilmenite grains. In these grains, the Cr2O3, MgO, V2O3, and Al2O3 contents range between 16.69-56.72%, 0.54-17.33%, 0.14-0.58%, and 1.33-38.79% respectively. Although they are rarely met in the ilmenite concentrate, the relatively finer grain sizes could lead to the separation of some with ilmenite fraction rather than with the ferromagnetic one. It is concluded that the problem of high Cr2O3 and Fe2O3 contents of the Egyptian beach ilmenite concentrate is not only a mineralogical problem, but also an ore-dressing one.